Pemanfaatan Inovasi Digital di bidang Pariwisata - Nindhia Hutagaol (Eduturisma, 2023)
In the era of digital innovations, the tourism industry is boldly evolving and replacing the traditional methods of traveling with an exciting and limitless virtual experience. This evolution occurs because the pace of technological change is so fast that it encourages all levels of the business and even the tourism industry to create creative ways to pursue business targets and expand expansion opportunities in this industry. The main objective of this research is to provide a comprehensive overview of advanced digital innovations from various studies related to the tourism sector. A systematic review of 551 articles published during 2020 - 2024 shows the collaboration of mobile devices with virtual reality/augmented reality technology is very profitable for users to explore any tourist attraction. This study of tourism technology development affects all layers of the tourism sector in terms of destination, infrastructure, promotion, service quality, and tourism safety. In addition to discussing the convenience provided by these various digital innovations, the findings of drawbacks and limits that arise in the implementation process will also discussed in this article. In the future, the development of digital tourism innovation requires involvement between industry stakeholders, namely policy makers, designers of technological innovations, and even end users to utilize the potential of today's technology so that new opportunities to create value in cultural tourism objects continue to grow and not being abandoned.